Evaluasi Kegunaan Web Elektronik Personal Health Record “My Nusahealth” dengan Metode Sistem Usability Scale (SUS) - Riska Pradita Satrio (Politeknik Kesehatan Bhakti Setya Indonesia, 2021)
Electronic personal health records system, often called E-PHR, is a systemthat contains personal health records that can be accessed at any time through a Web-enabled device, such as a computer telephone or PDA (Thede. L, 2008).Patients can quickly access test results, view examination and treatment history, and communicate with doctors. My Nusahealth is a web-based electronic Personal Health Record that is integrated with Electronic Medical Records in hospitals. The aim is to make it easier for patients to access their personal health data at the hospitals they have visited. To ensure that the My Nusahealth application is in accordance with the needs of users both by patients and hospitals as health facility providers, it is necessary to evaluate the level of usability. The evaluation method used to assess the My Nusahealth application is the System Usability Scale (SUS) because this method has advantages over other methods. This research is a type of accidental quantitative research (accidental sampling). Data collection was carried out by distributing a questionnaire link in the form of a google form to respondents via social media and WhatsApp. The My Nusahealth application can be accessed by respondents at: http://bit.ly/MyNusaHealth. The research sample was 10 (ten) people who were selected using the Systematic Random Sampling technique. The results of the final calculation of the SUS score in table 5 above were 73. While the average SUS score was 68, this means that the score obtained from evaluation of the use of the My Nusahealth Web is above the average global SUS score. Based on these final results, Web My Nusahealth has acceptability ranges in the acceptable category, the grade scale in the C category and an adjective rating in the good category.